An innovative self-adaptive method for improving heat sink utilization efficiency of hydrocarbon fuel in regenerative thermal protection system of combined cycle engine. (15th December 2018) - Jing, Tingting; He, Guoqiang; Qin, Fei; Li, Wenqiang; Zhang, Duo; Zhang, Pengkun
Highlights: Innovative self-adaptive method is proposed for improving heat sink utilization. Jet flow and virtual throat adapt with channels' flow and thermal differences. X  = 200 mm obtains the most uniform distribution with 10% and 20% heat deviations. More adaptive mini-structure can obtain more uniform mass flow rate distribution. Abstract: A highly efficient regenerative thermal management system of combined cycle engine can realize the energy balance between the high power requirement of the vehicle and severe thermal environment of the engine, therefore, the heat sink utilization efficiency of supercritical hydrocarbon fuel in regenerative thermal protection system needs to be improved. In this paper, an innovative self-adaptive method using mini-structure to improve the mass flow rate distribution in thermal protection system with parallel cooling channels is proposed based on the engine's extremely nonuniform thermal load. The effectiveness of this novel method is numerically studied, and the effects of adaptive mini-structure's location and number are also investigated. The results demonstrate that the existence of adaptive mini-structure improves the mass flow uniformity between parallel channels by forming a jet flow through the mini-structure and the backward recirculation region created by the jet flow, these two characteristics adaptively change the flow area in the low heat flux channel and create a virtual throat after the adaptive mini-structure which decreases the mass flow rate in low heat flux channel and achieves better uniformity. Among the various cases in the present paper, the location with X  = 200 mm improves the uniformity of parallel channels with 10% deviation of heat flux from 26.6% to 78.8%, and for the 20% deviation of heat flux, the uniformity is improved from 23.5% to 63.4%.